2001
DOI: 10.1097/00006534-200110000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Single Dose of 5-Fluorouracil on Keloid Scars: A Clinical Trial of Timed Wound Irrigation after Extralesional Excision

Abstract: The possibility of altering the pathophysiology of keloid scars was investigated in 11 patients, using a single application of 5-fluorouracil solution for 5 minutes after extralesional excision was performed. Similar excisional wounds treated with phosphate-buffered saline for 5 minutes served as synchronous controls. An objective scoring system and subjective assessment were made to assay the change in the quality of the wound-healing and scar tissue produced by this treatment. A keloid scar score was used at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 16 publications
1
58
0
2
Order By: Relevance
“…In the early 1980s, 5-FU was investigated as an adjunct to glaucoma filtering surgery, a procedure in which inhibition of wound healing is desirable to achieve surgical success (Gressel et al, 1984;Skuta et al, 1987). More recently, local 5-FU application has shown some success in the treatment and prevention of hypertrophic scars and keloids (Fitzpatrick 1999;Uppal et al, 2001).…”
mentioning
confidence: 99%
“…In the early 1980s, 5-FU was investigated as an adjunct to glaucoma filtering surgery, a procedure in which inhibition of wound healing is desirable to achieve surgical success (Gressel et al, 1984;Skuta et al, 1987). More recently, local 5-FU application has shown some success in the treatment and prevention of hypertrophic scars and keloids (Fitzpatrick 1999;Uppal et al, 2001).…”
mentioning
confidence: 99%
“…Curative treatment of keloids is difficult, and a plethora of treatment options has been studied. Treatment modalities include compression therapy, cryosurgery, injections (steroids, mitomycin C, 5-fluorouracil, interferon, or PRP), surgery, and postoperative radiotherapy, depending on the size and location of the keloid scar [3][4][5][6]. Studies have found that keloid treatment is most effective when using multiple modalities, but there is still much controversy as to what is the optimal treatment [7].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal scars may cause pain or pruritus, disturb the range of motion, diminish sensation, or cause aesthetic deformities that may lead to significant psychosocial distress. Treatment modalities include compression therapy, cryosurgery, injections (steroids, mitomycin C, 5-fluorouracil, interferon, or platelet-rich plasma [PRP]), surgery, and postoperative radiotherapy, depending on the size and location of the keloid scars [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The increased rate of proliferation seen in keloidal fibroblasts suggests that 5-FU may be effective in limiting keloid growth [14]. A major drawback of systemic 5-FU is its association with anemia, leucopenia, and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%